Konseling Individual dengan Teknik Meditasi Jantung untuk Mengatasi Self Harm pada Pengidap Bipolar di RSJD dr. Arif Zainudin - Ri'ayatun Najah; Alfin Miftahul Khairi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2024)
This research aims to analyze the role and effectiveness of individual counseling services using heart meditation techniques to overcome self harm in bipolar sufferers at RSJD dr. Arif Zainudin. The method used in this research is qualitative with a case study approach and data collection through interviews, observation and documentation. Then the researchers used a sampling strategy in the form of purposive sampling and have studied intensively about the background of bipolar sufferers who carry out bad coping in the form of self-harm as well as heart meditation techniques which are an alternative to overcome them. Individual counseling with heart meditation techniques is part of transpersonal psychology which refers to the relationship between psychology and spirituality. This is in line with the saying that the spiritual heart and heart (qalbu) are located between the nafs and the spirit and function to regulate the physical and psychological. The results showed that three subjects in this study were able to divert bad self-harm coping with positive activities such as meditation, mindfulness breathing therapy, yoga and exercise from ten populations who had also succeeded in understanding that the body is a valuable thing. Therefore, individual counseling is the right alternative to overcome self-harm in bipolar sufferers who lose self-control through the awareness that the heart is a gift from God and a place of divine spark through heart meditation techniques.